Gaps in the Implementation of the Non-Prima Facie Refugee Status Determination in Uganda (African Human Mobility Review, 2025)
Refugee status determination is an important initial step in protecting people seeking asylum and in determining who is entitled to international and national protection under refugee law. Refugee status determination gives access to the individuals/groups seeking asylum protection under international or national laws, grants legal certainty, protects them from refoulement and provides a pathway to integration—not just as a humanitarian act but as a human right. Uganda offers refugee protection to millions of refugees, most arriving in large numbers having fled conflict in neighboring countries. The majority of these asylum seekers are assisted at reception sites along the borders through a prima facie process. This process is accessible and largely efficient. Although much smaller in number, there are also a significant number of refugees whose applications are processed through a non-prima facie status determination. Such asylum seekers arrive as individuals or small family groups and often in urban contexts. Despite legal frameworks that provide for individual applications, the non-prima facie process faces significant barriers or gaps in its implementation. This is further exacerbated by the fact that the non-prima facie process is mostly invisible in both national and international research and in the government agenda. This article explores the barriers and the gaps in the non-prima facie refugee status determination process in Uganda.